A STUDY OF THE ROLE OF CUSTOMER RELATIONSHIP MANAGEMENT AS A COMPETITIVE ADVANTAGE IN GREEN MARKETING - Reza Esmaeilpour; Ramezanali Mobasher Amini; Amini Nazanin Emamgholi (Spektrum Industri, 2012)
Customer relationship management is considered as a strategic necessity in all organizations. Today, companies and organizations have to consider the preservation of environment in their activities in order to gain customers’ satisfaction, perform social responsibilities, and protect consumers’ rights. Regarding these green marketing mixtures, the present research aims at studying the role of customer relationship management as a competitive advantage in green marketing on health and cosmetic products. Here, four marketing mixtures (product, promotion, place, and price) were defined as the research variables. Out of the total subjects that included all shops selling these products in the city of Rasht, a sample population of 131 shopkeepers was chosen to indicate the degree of their attention to selling green products and the degree of customers’ attention to buying green products. The present research is an analytic-descriptive one. A researcher- made questionnaire standardized through Cronbach’s alpha was used to collect data. Then, the data collected were analyzed by SPSS 15, t-test of tow independent samples, and variance analysis. It was finally indicated that there was meaningful relationship between customer relationship management and the mixture elements of green marketing. Key terms: Customer relationship management, Green marketing, Competitive advantage, Green marketing mixture